Analysis of a Residential Distribution System with the Application of Conservation Voltage Reduction at House Level - Selamogullari, Ugur S.; Alsaad, Alaa (IEEE, 2019)
With the advancement of communication technologies and big data concept, the conventional grid has been transformed to a smart grid. The smart grid concept provides two-way information flow and dynamic control of the generation and consumption is possible through this information exchange. Within the smart grid, residential customers can also become smart and can be treated as an active demand. Thus, demand response algorithms-such as load shifting, load shedding- are being used to control the residential demand. Recently, the conservation voltage reduction (CVR), which is mainly used at distribution system level, has emerged as another way of demand response application at house level. In this study, the effect of the CVR at house level on a residential distribution system power demand and distribution losses are analyzed for a system with 14 houses. ZIP models of common residential appliances are used to obtain MATLAB/Simulink model of the house level CVR application. Obtained results show that the power demand is reduced by about 20% and the distribution losses is reduced by about 35% when the CVR is applied at house level as a demand response method.
Keywords: Smart home; demand response; CVR at house level; residential distribution system; ENERGY; IMPLEMENTATION; CVR; Energy & Fuels; Engineering